2009
DOI: 10.1016/j.biocel.2009.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria in cardiomyocyte Ca2+ signaling

Abstract: Ca2+ signaling is of vital importance to cardiac cell function and plays an important role in heart failure. It is based on sarcolemmal, sarcoplasmic reticulum and mitochondrial Ca2+ cyclings. While the first two are well characterized, the latter remains unclear, controversial and technically challenging. In mammalian cardiac myocytes, Ca2+ influx through L-type calcium channels in the sarcolemmal membrane triggers Ca2+ release from the nearby junctional sarcoplasmic reticulum to produce Ca2+ sparks. When thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 273 publications
(395 reference statements)
1
73
0
5
Order By: Relevance
“…It has been suggested that IFM primarily supply ATP for the contractile system, whereas SSM provide the energy for the transport of electrolytes and metabolites across the sarcolemma [71]. IFM are also central for mitochondrial Ca 2+ cycling due to their proximity to the sarcoplasmic reticulum [72].…”
Section: Regulation Of Mitochondrial Biogenesis In Heartmentioning
confidence: 99%
“…It has been suggested that IFM primarily supply ATP for the contractile system, whereas SSM provide the energy for the transport of electrolytes and metabolites across the sarcolemma [71]. IFM are also central for mitochondrial Ca 2+ cycling due to their proximity to the sarcoplasmic reticulum [72].…”
Section: Regulation Of Mitochondrial Biogenesis In Heartmentioning
confidence: 99%
“…More specifically, in fast-glycolytic muscle, mitochondria are likely exposed to large increases in matrix [Ca 2ϩ ] compared with mitochondria from slow-oxidative muscle due to: 1) the large and rapid Ca 2ϩ surges that occur during contractions (21); 2) the physical proximity of mitochondria to large SR Ca 2ϩ stores (64,72,102); and 3) the small mitochondrial volume density and thus the low distribution volume for Ca 2ϩ in the matrix (12) (Fig. 3D).…”
Section: C634mentioning
confidence: 99%
“…3D). In fast-glycolytic fibers, a higher Ca 2ϩ threshold for PTP opening may ensure proper operation of the PTP in the flickering mode [which regulates ⌬⌿, ROS production and Ca 2ϩ signaling waves (17,28,64)], and prevention of accidental switch to the high-conductance mode involved in cell death signaling. Further work is, however, required to validate this hypothesis.…”
Section: C634mentioning
confidence: 99%
“…This is expected since Ca 2+ release from the sarcoplasmic reticulum which underlies cardiac contraction in general is triggered and coordinated with the entry of Ca 2+ from the cytoplasm. 28 As Na + channel blocker, Quinidine affects the inward Na + flux and the fast depolarization phase of cardiac action potential which delays the activation of K + channels and Ca 2+ channels. Thus, it prolongs the cardiac potential and subsequently prolongs the beat interval.…”
Section: Drug Screening Applicability Of the Combined Methodsmentioning
confidence: 99%